Histiocytic sarcoma as a secondary malignancy: pathobiology, diagnosis, and treatment. (8th April 2016) - Ansari, Junaid; Naqash, Abdul Rafeh; Munker, Reinhold; El‐Osta, Hazem; Master, Samip; Cotelingam, James D.; Griffiths, Elizabeth; Greer, Adam H.; Yin, Hong; Peddi, Prakash; Shackelford, Rodney E.
Abstract: Histiocytic sarcoma (HS) is an extremely rare non‐Langerhans cell disorder with an aggressive course and limited treatment options. Recent advances in molecular/genetic sequencing have suggested a common clonal origin between various hematolymphoid disorders and cases of secondary HS. Deriving conclusions from previously reported cases of HS arising secondarily to certain hematolymphoid disorders, here we have tried to provide insight into the mechanisms influencing this evolution. We also discuss a clinical case of a 72‐year‐old man with a diagnosis of chronic myeloid leukemia (CML), presenting subsequently with a heterogeneous liver mass positive with a diagnosis of HS. The liver mass showed a retained BCR‐ABL1 translocation suggesting clonality between the CML and HS. As seen in our case and other reported cases of HS derived secondarily, the concurrent expression of immunoglobulin heavy (IGH)‐/light‐chain rearrangements or cytogenetic markers common to the primary malignancy suggests an evolutionary mechanism involving lineage switching that could potentially be influenced by genetic or epigenetic cues which may occur at the level of a progenitor or the malignant cell itself.